Hepatobiliary Tract and Pancreatic Disorders in Celiac Disease - Hugh J Freeman (Canadian Journal of Gastroenterology)
A number of hepatobiliary tract and pancreatic disorders have been documented in patients with celiac disease. Some disorders have shared immunological or genetic factors, including chronic hepatitis, primary biliary cirrhosis and sclerosing cholangitis. Other hepatic or pancreatic pathological changes in celiac disease have been documented with severe malnutrition and malabsorption, including hepatic steatosis and pancreatic insufficiency, sometimes with pancreatic calcification. Finally, celiac disease may be associated with other very rare hepatic complications, such as hepatic T cell lymphoma.